Study of the behavior of some biomechanical characteristics during the launch, in baseball pitchers of the Sancti Spiritus team(Original) (Revista científica Olimpia, 2020)
The work offers the results achieved in a biomechanical study carried out on two pitchers of the provincial team of seniors of Sancti Spiritus, who were part of the national preselection, for the 53 Baseball Series in Cuba, due to the need that the launch coaches have, to determine precisely where the difficulties lie in the execution of the movements of their athletes, those that they cannot detect only by direct observation and that they need to know, to solve them if possible. With the support of observation and measurement methods, the use of videographic techniques and Kinovea movement analysis software, it was possible to perform the analysis and detect deficiencies in the execution of the launch, providing elements to the trainers, which will allow them to direct with more efficient control of the technical preparation of these launchers.
Keywords: biomechanical characteristics; technical execution; phases and subphases of the launch.